Implementation of Organizational Management in Pesantren Educational Activities: A Case Study at Pesantren Bina Insani, Yogyakarta - Naufal Ahmad Rijalul Alam; Asmaji Muchtar; Choeroni (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
This research explores implementing organizational management within educational activities at Pesantren Bina Insani in Yogyakarta. The study analyzes how effective management practices influence the academic outcomes and overall functioning of the pesantren, a traditional Islamic boarding school in Indonesia. Data was collected via interviews, observations, and document analysis through a qualitative case study approach. The findings reveal that effective organizational management is crucial in facilitating a conducive learning environment, enhancing student engagement, and promoting the professional development of educators. Key management strategies identified include structured planning, clear communication channels, and active involvement of stakeholders in decision-making processes. The study concludes that successfully implementing organizational management principles significantly contributes to the quality of educational activities in pesantren settings. Recommendations for improving management practices in similar institutions are also discussed, emphasizing the need for continuous evaluation and adaptation to meet the evolving educational demands. This research contributes to the broader understanding of how organizational management can enhance educational effectiveness in Islamic boarding schools, providing valuable insights for educators, administrators, and policymakers.